Bibliometric Analysis of Islamic Education Management Research Trends in Indonesia (2015-2025): Identifying Gaps and Strategies for Development - Aminudin, Aminudin; Cahyani, Dewi; Munawaroh, Mumun; Arifudin, Iis (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze trends and developments in Islamic education management research in Indonesia from 2015 to 2025. The method employed is bibliometric analysis, utilizing a quantitative approach. This study includes 107 documents published by 371 authors, with an average document age of 3.02 years. This bibliometric analysis uses VOSviewer and Biblioshiny software. This study found a significant surge in Islamic Education Management publications in Indonesia, with an annual growth rate of 21.48%, particularly in 2022 and 2023, and a notable contribution from religious universities, such as UIN Sunan Kalijaga. The change in topics indicates a shift from a normative approach towards digitalization, interdisciplinarity, and technology-based institutional strategies, including responses to crises such as the pandemic. However, a significant gap remains in integrative studies that combine applied science with cutting-edge research technology, presenting strategic opportunities for the future development of Islamic Education Management research. This research provides a data-driven reference for developing a national research strategy in Islamic Education Management and a roadmap for scientific collaboration. Further research can focus on strengthening interdisciplinary research, integrating digital technologies, and collaborative networks across countries and institutions.